1997
DOI: 10.1002/(sici)1097-0142(19970115)79:2<214::aid-cncr3>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Direct measurement of doxorubicin concentration in the intact, living single cancer cell during hyperthermia

Abstract: Hyperthermia increased the uptake of doxorubicin in the nuclei of cancer cells. Thus, the authors concluded that hyperthermia increases the cells' sensitivity to the drug.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…The time‐dependent cellular uptake of the loaded DOX was also seen since much stronger fluorescence was seen after 4 h than after 1 h. However, fluorescence could be detected both in the cytoplasm and nucleus for the DOX loaded micelles after both 1 h and 4 h. This is in accordance with the different cellular uptake ways. Free DOX quickly diffused through the cell membrane and concentrated in the nuclei,23 while the DOX loaded micelles were taken up via the endocytosis pathway,24 thus distribution in both cytoplasm and nucleus was observed.…”
Section: Resultsmentioning
confidence: 99%
“…The time‐dependent cellular uptake of the loaded DOX was also seen since much stronger fluorescence was seen after 4 h than after 1 h. However, fluorescence could be detected both in the cytoplasm and nucleus for the DOX loaded micelles after both 1 h and 4 h. This is in accordance with the different cellular uptake ways. Free DOX quickly diffused through the cell membrane and concentrated in the nuclei,23 while the DOX loaded micelles were taken up via the endocytosis pathway,24 thus distribution in both cytoplasm and nucleus was observed.…”
Section: Resultsmentioning
confidence: 99%
“…Using an elegant confocal approach, Kawai et al, demonstrated that 43 C hyperthermia increased the accumulation of doxorubicin into the nuclei of both drug-sensitive and drug-resistant oesophageal carcinoma cell lines [62]. The enhancement in uptake was 4.3 and 7.2-fold for the drug-sensitive and drug-resistant lines.…”
Section: Doxorubicinmentioning
confidence: 99%
“…For many tumour cell lines, doxorubicin is actively pumped out of cells by the multi-drug resistance membrane protein, which can be transiently damaged by heat 85,86 . Hence, transient hyperthermic damage to cellular homeostatic mechanisms that permit increased cellular or nuclear membrane permeability to doxorubicin and increased intracellular accumulation could be partly responsible 87,88 . Alternatively, RF has been shown to transiently reduce blood flow at 45-50 C 83 and cellular uptake of doxorubicin is known to increase under hypoxic conditions 89 .…”
Section: Improved Cytotoxicity Of Doxorubicinmentioning
confidence: 99%